The topochemical reduction of ru-containing double perovskite oxides - Liang, Z (2023)
This work focuses on the topochemical reduction of some ruthenium-containing double perovskite phases using various reducing agents (Zr, LiH, CaH2) to form novel metastable reduced phases and anion-substituted phases.